Sosialisasi K3 pada Pekerjaan Bangunan Sederhana di Desa Naumbai - Islah, Muhammad; Febryanto; Supriadi, Jefri (Faculty of Engineering University of Pahlawan Tuanku Tambusai, 2024)
Occupational Safety and Health (K3) is one of the important aspects in the construction world that is often overlooked, especially in simple building projects in rural areas. This program aims to socialize the importance of occupational safety and health (K3) to simple construction workers in Naumbai Village. The material presented includes the use of personal protective equipment (PPE), identification of potential hazards in the work environment, safe work procedures, and mitigation of work accident risks. The activity is carried out through three main stages, namely preparation, implementation, and evaluation. The implementation stage includes counseling to workers, simulation of the use of PPE, group discussions, and distribution of educational media. Evaluation is carried out by filling out questionnaires and interviews with workers, field staff, and project managers. The results of the community service show that understanding of K3 is quite high among field and managerial staff, but still low among casual laborers. As many as 70% of managerial staff and 72% of field staff showed support for the implementation of K3, while only 65% ​​of construction workers agreed and actually implemented the principles of K3.